Earnings deviation of interim and annual accounts: pre and post-MASB 26 - Fauzi Saidin, Saidatunur; Malek, Mazrah; Phua, Lian Kee (Inderscience Enterprises Ltd., 2022)
This study is to examine whether the use of discrete method may enhance the quality of interim financial accounts. It examines whether the magnitude and occurrence of earnings deviation post-MASB 26 is significantly lower than pre-MASB 26. Data is based on listed companies on Bursa Malaysia for two years before and after the introduction of MASB 26 in 2002. The t-test shows that the magnitude of earnings deviation pre-MASB 26 is significantly higher as compared to post-MASB 26. Sub-sample analyses also showed that the magnitude of both overstated and understated companies is significantly higher pre-MASB 26. However, Pearson chi-square shows that the occurrence of earnings deviation has increased post-MASB 26 which was contributed to by the increase in occurrence of understated quarterly earnings. This study provides evidence that the use of discrete method might enhance the quality of interim reporting. Whilst, alternative methods of accounting provide different benefits and drawbacks, this study highlighted the need for regulators to consider the objective of financial reporting in formulating the accounting standards.